2006
DOI: 10.2170/physiolsci.rp010806
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide, a Blocker of Na+/K+/2Cl− Cotransporter, Diminishes Proliferation of Poorly Differentiated Human Gastric Cancer Cells by Affecting G0/G1 State

Abstract: Furosemide, a blocker of Na + /K + /2Cl -cotransporter (NKCC), is often used as a diuretic to improve edema, ascites, and pleural effusion of patients with cancers. The aim of the present study was to investigate whether an NKCC blocker affects cancer cell growth. If so, we would clarify the mechanism of this action. We found that poorly differentiated gastric adenocarcinoma cells (MKN45) expressed the mRNA of NKCC1 three times higher than moderately differentiated ones (MKN28) and that the NKCC in MKN45 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 28 publications
0
54
2
1
Order By: Relevance
“…Although the mechanisms involved in proliferation of b-cells lacking NKCC1 remain unknown, our findings are in contrast to the direct positive linear relationship that exists between b-cell mass and body weight (Montanya et al 2000, Herbach et al 2011 and to the known negative impact that pharmacological inhibition of NKCC1 or depletion of [Cl K ] i have on normal cell growth and proliferation (O'Brien et al 1988, Panet et al 1994, 2002, Lang et al 1998, Iwamoto et al 2004, Shiozaki et al 2006. Indeed, NKCC1 KO mice are half the weight of NKCC1…”
Section: Discussioncontrasting
confidence: 77%
“…Although the mechanisms involved in proliferation of b-cells lacking NKCC1 remain unknown, our findings are in contrast to the direct positive linear relationship that exists between b-cell mass and body weight (Montanya et al 2000, Herbach et al 2011 and to the known negative impact that pharmacological inhibition of NKCC1 or depletion of [Cl K ] i have on normal cell growth and proliferation (O'Brien et al 1988, Panet et al 1994, 2002, Lang et al 1998, Iwamoto et al 2004, Shiozaki et al 2006. Indeed, NKCC1 KO mice are half the weight of NKCC1…”
Section: Discussioncontrasting
confidence: 77%
“…These reports suggest that the changes in the [Cl -]i might act as a regulator of various types of intracellular enzymes. We previously showed that furosemide, a blocker of NKCC, diminished cell growth by delaying the G1-S phase progression in gastric cancer cells with high expression and activity of NKCC [12] (Figure 1 [17,18] . These findings indicated that our experimental system using the low Cl -medium can be used as a model of the [Cl -]i regulation (Figure 2).…”
Section: Transductionmentioning
confidence: 97%
“…-cotransporter (NKCC) were higher in poorly-differentiated type gastric adenocarcinoma cells than in differentiated cells [12] . These reports indicate that the transepithelial Cl -transport plays an important role in cell proliferation of gastrointestinal cancer cells.…”
Section: Editorialmentioning
confidence: 98%
“…These findings clearly support the efficacy of pleural lavage with distilled water during surgery for ESCC. The coverslip with the cells was set in a perfusion chamber that was mounted on the stage of a DIC microscope (BX50Wi, Olympus, Tokyo, Japan) connected to a video-enhanced contrast (VEC) system (ARGUS-20, Hamamatsu Photonics, Hamamatsu, Japan), and images were continuously recorded by a video recorder according to the procedure described previously (9). The experiments were performed at 37˚C.…”
Section: Introductionmentioning
confidence: 99%